2021
DOI: 10.3390/cancers13122942
|View full text |Cite
|
Sign up to set email alerts
|

Life after Cell Death—Survival and Survivorship Following Chemotherapy

Abstract: To prevent cancer cells replacing and outnumbering their functional somatic counterparts, the most effective solution is their removal. Classical treatments rely on surgical excision, chemical or physical damage to the cancer cells by conventional interventions such as chemo- and radiotherapy, to eliminate or reduce tumour burden. Cancer treatment has in the last two decades seen the advent of increasingly sophisticated therapeutic regimens aimed at selectively targeting cancer cells whilst sparing the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 166 publications
(252 reference statements)
0
2
0
Order By: Relevance
“…Radiation exposure activates an immune response, determining the activation of macrophages and the recruitment of neutrophils and lymphocytes and pro-inflammatory mediators’ production in order to support anti-tumor activity [ 14 , 15 ]. After irradiation, chemotherapy, or Hematopoietic stem cell transplantation (HSCT) long-term immune system alteration could persist [ 16 , 17 ]. Some studies have shown that compared with controls, survivors who underwent HCT for a primary hematologic malignancy at age ≤21 had a similar BMI but a higher percent fat mass [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation exposure activates an immune response, determining the activation of macrophages and the recruitment of neutrophils and lymphocytes and pro-inflammatory mediators’ production in order to support anti-tumor activity [ 14 , 15 ]. After irradiation, chemotherapy, or Hematopoietic stem cell transplantation (HSCT) long-term immune system alteration could persist [ 16 , 17 ]. Some studies have shown that compared with controls, survivors who underwent HCT for a primary hematologic malignancy at age ≤21 had a similar BMI but a higher percent fat mass [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, exposure to oncological therapies (mainly chemo- and radiotherapy) causes low-grade systemic inflammatory state onset, senescent cell accumulation, the increased production of reactive oxygen species (ROS), immune response activation and DNA mutations [ 4 , 5 ]. This global inflammatory condition is known as “inflamm-aging” to indicate the correlation between inflammatory processes—exacerbated in CCS subjects—and the observed pathological conditions displayed by young adult CCS even though they are characteristic of an elder age [ 6 ].…”
mentioning
confidence: 99%